Accuracy of the Informant Questionnaire on Cognitive Decline in the Elderly for Detecting Preexisting Dementia in Transient Ischemic Attack and Stroke: A Population-Based Study. Issue 4 (8th March 2021) - van Nieuwkerk, Astrid C.; Pendlebury, Sarah T.; Rothwell, Peter M.; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Prestroke dementia prevalence is high and impacts outcome. Although the IQCODE (Informant Questionnaire on Cognitive Decline in the Elderly) is being used to assess prestroke cognition, data on its validity for prestroke dementia are lacking. We studied the accuracy of the short-form (16-item) IQCODE for pre-event dementia in a population-based study of all transient ischemic attack (TIA)/stroke. Methods: All patients with TIA/stroke in a defined population of ≈92 720 (Oxford Vascular Study, 2002–2017) with IQCODE were included. IQCODE questionnaires were given to participants at baseline interview with instructions to pass to an informant for completion and return by post. Diagnosis of pre-event dementia was defined as prior diagnosis of dementia, or dementia by the Diagnostic and Statistical Manual of Mental Disorders-IV criteria on study interview and hand-searching of the entire medical record blinded to IQCODE. Reliability of the IQCODE for dementia was determined by the area under the receiver operating characteristic curve, sensitivity and specificity, stratified by age, event severity, and first-ever stroke. Results: Among 2059 interviewed survivors, IQCODE were returned in 1068 (mean age/SD=72.9/12.3, 47% TIA, 52.3% male, 68 [6.4%] pre-event dementia). Area under the receiver operating characteristic curve for IQCODE for pre-event dementia was 0.94 (95% CI, 0.90–0.97, P <0.001) with similar results by age: 0.92, 0.88 to 0.96, <65 years; 0.94, 0.83 to 1.00, 65 to 74 years; 0.95, 0.92 to 0.99, 75 to 84 years; 0.89, 0.82 to 0.96, ≥85 years. The optimal cutoff score overall was >3.48 (sensitivity=89.7%; specificity=84.2%) but was nonsignificantly higher for major stroke (National Institutes of Health Stroke Scale score ≥3) than minor stroke/TIA (>3.85 versus >3.47). Performance was similar in patients with first-ever stroke (area under the receiver operating characteristic curve, 0.92 [0.88–0.97]; sensitivity=85.7%; specificity=84.8% for cutoff >3.48). All 16-IQCODE questions discriminated between dementia and no dementia (all P <0.001) with the greatest differences seen for finances, using gadgets, arithmetic, and learning new things. Conclusions: IQCODE has excellent accuracy for detecting preexisting dementia in TIA and stroke with the pattern of deficits suggesting prominent executive dysfunction.